How performance based payoffs influence estimates of complex information? An experimental study on quality and precision in estimation tasks - Eike Benjamin Kroll; Jörg Rieger; Bodo Vogt (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2011)
This paper investigates the processing of repeated complex information. The focus of this study is, whether additional information and the introduction of performance-based payoffs have an influence on judgement. Therefore, an experiment is designed to investigate the degree of precision and quality of interval estimates. The data shows that providing additional information decreases the precision of stated estimates, while it improves its quality. The same result is obtained, when performance-based payoffs are introduced to an otherwise hypothetical decision environment. That means, while the variation in the treatment variables increase the quality of the estimate, the precision as a reflection of the decision makers confidence is reduced.
urn:nbn:de:swb:90-224784
Keywords: C90; C91; C92; D81; 330; interval estimates; uncertainty; judgmental estimation; repeated information; hypothetical versus payoffs; experiment